VISITORS PERCEPTION OF THE FUNCTION OF THE FOREST IN MAROS CITY - Mukhsin Mukhsin; Rosmini Maru; Sulaiman Zhiddiq (UNM Geographic Journal, 2021)
This study aims : (1) To find out how the community activities that visit the Maros City Forest. (2) To find out the perception of the people who use the Maros City Forest . This research is a quantitative descriptive study with the object of research is the entire area of the City of Maros Forest while the sample is a visitor from the City of Maros Forest . Data collected through interviews, questionnaires and documentation. The results obtained (1) Community activities that come to the city of Maros Forest most to exercise and visitors who almost every day come to sell food and drinks. (2) Community perceptions of the main functions of urban forests are quite good and community perceptions for additional functions of the Maros City Forest are also quite good.